Out of ERmita ; Sunken San Diego Making it [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Manila Mayor Alfredo Lim's drive to eradiate prostitution. The galleon ship San Diego was discovered in the waters of Batangas with its reasures still intact. Mon David making it to the music industry.